The Chemical Synergy of Greenhouse Gases and Cost-Effectiveness Analysis for Climate Mitigation Strategies - Yang, Xiwen (International Journal of Natural Resources and Environmental Studies, 2025)
Global warming is a serious challenge facing the world today. This study confirms that greenhouse gas emissions from human activities are the main driving factors. By systematically analyzing the source-sink balance of greenhouse gases such as carbon dioxide (CO2) and methane (CH4), it is clarified that the significant imbalance caused by the surge in emissions and the weakening of carbon sink capacity is the key mechanism for accelerated climate warming. Furthermore, from the perspective of chemical reaction kinetics, the synergistic effects among the three key greenhouse gases of hydroxyl radical (OH) regulation mechanism, nitrogen cycle cascade effect and sulfate aerosol effect were explained. On this basis, the economic benefit index (CEI) is innovatively constructed, and the above synergistic effects are integrated into the accounting framework. Taking CO and CH as an example, the paradigm of quantitative analysis using CEI is set up, and it is speculated that the synergistic reaction can significantly improve the CEI estimation. Finally, based on the quantitative results of CEI, a differentiated emission reduction strategy is proposed: give priority to the implementation of high CEI measures, and plan the long-term development path of low CEI technology. This study constructs a complete research system from cause analysis, chemical mechanism exploration to economic evaluation and strategy formulation, aiming to provide a theoretical framework and decision support for global climate governance.